Elastin-specific MRI of extracellular matrix-remodelling following hepatic radiofrequency-ablation in a VX2 liver tumor model - Collettini, Federico; Reimann, Carolin; Brangsch, Julia; Chapiro, Julius; Savic, Lynn Jeanette; Onthank, David C.; Robinson, Simon P.; Karst, Uwe; Buchholz, Rebecca; Keller, Sarah; Hamm, Bernd; Goldberg, S. Nahum; et al. (Scientific Reports, 2021)
Hepatic radiofrequency ablation (RFA) induces a drastic alteration of the biomechanical environment in the peritumoral liver tissue. The resulting increase in matrix stiffness has been shown to significantly influence carcinogenesis and cancer progression after focal RF ablation. To investigate the potential of an elastin-specific MR agent (ESMA) for the assessment of extracellular matrix (ECM) remodeling in the periablational rim following RFA in a VX2 rabbit liver tumor-model, twelve New-Zealand-White-rabbits were implanted in the left liver lobe with VX2 tumor chunks from donor animals. RFA of tumors was performed using a perfused RF needle-applicator with a mean tip temperature of 70 °C. Animals were randomized into four groups for MR imaging and scanned at four different time points following RFA (week 0 [baseline], week 1, week 2 and week 3 after RFA), followed by sacrifice and histopathological analysis. ESMA-enhanced MR imaging was used to assess ECM remodeling. Gadobutrol was used as a third-space control agent. Molecular MR imaging using an elastin-specific probe demonstrated a progressive increase in contrast-to-noise ratio (CNR) (week 3: ESMA: 28.1 ± 6.0; gadobutrol: 3.5 ± 2.0), enabling non-invasive imaging of the peritumoral zone with high spatial-resolution, and accurate assessment of elastin deposition in the periablational rim. In vivo CNR correlated with ex vivo histomorphometry (ElasticaVanGiesson-stain, y = 1.2x − 1.8, R2 = 0.89, p < 0.05) and gadolinium concentrations at inductively coupled mass spectroscopy (ICP-MS, y = 0.04x + 1.2, R2 = 0.95, p < 0.05). Laser-ICP-MS confirmed colocalization of elastin-specific probe with elastic fibers. Following thermal ablation, molecular imaging using an elastin-specific MR probe is feasible and provides a quantifiable biomarker for the assessment of the ablation-induced remodeling of the ECM in the periablational rim.
CRIS-Team Scopus Importer:2023-03-08